2016
DOI: 10.7717/peerj.2557
|View full text |Cite
|
Sign up to set email alerts
|

Variation in habitat soundscape characteristics influences settlement of a reef-building coral

Abstract: Coral populations, and the productive reef ecosystems they support, rely on successful recruitment of reef-building species, beginning with settlement of dispersing larvae into habitat favourable to survival. Many substrate cues have been identified as contributors to coral larval habitat selection; however, the potential for ambient acoustic cues to influence coral settlement responses is unknown. Using in situ settlement chambers that excluded other habitat cues, larval settlement of a dominant Caribbean ree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…These studies have found suggestive differences in the acoustic signatures of healthy versus degraded habitats, but such differences may just as likely be based upon the variation in biological communities. The playback of healthy coral reef habitat sounds also results in greater attraction by the settlement stages of coral, mollusk, and coral reef fish larvae, which are migrating from offshore [5][6][7][8]11,106].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies have found suggestive differences in the acoustic signatures of healthy versus degraded habitats, but such differences may just as likely be based upon the variation in biological communities. The playback of healthy coral reef habitat sounds also results in greater attraction by the settlement stages of coral, mollusk, and coral reef fish larvae, which are migrating from offshore [5][6][7][8]11,106].…”
Section: Discussionmentioning
confidence: 99%
“…Power spectral density (PSD) was the most commonly used [3,7,[17][18][19]21,22,38,43,46,59,61,63,64,[66][67][68]. Sound pressure level (SPL), or root mean square (RMS)-SPL, were the next most frequently used parameters [6,8,11,17,20,21,38,53,54,59,61,63,64,68,69]. SPL is a logarithmic summary measure of the ratio of the pressure of a sound relative to a reference value and results in a measurement in decibels (dB).…”
Section: Acoustic Parameters and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether reefs can recover from these disturbances will depend, in part, on the supply of colonists available to settle to newly opened space that appears on reefs following a disturbance (Gilmour et al, 2013). Both stochastic processes which affect the supply of potential colonists and deterministic processes such as habitat availability, larval preferences, and interactions with existing community members, can influence settlement patterns (Lillis et al, 2016). Post-settlement processes then further shape subsequent community development (Caley et al, 1996).…”
Section: Introductionmentioning
confidence: 99%